CHALLENGES OF SCHOOL INCLUSION FOR CHILDREN WITH TEAT IN EARLY CHILDHOOD EDUCATION (Editora Impacto Científico, 2025)
This article discusses the challenges of including children with Autism Spectrum Disorder (ASD) in early childhood education, highlighting the multiple dimensions involved in this process. Based on bibliographical research, aspects related to public policies, teacher training, school infrastructure, family-school relations and inclusive pedagogical practices were analyzed. The study shows that, despite legal and regulatory advances, there are still significant barriers that make it difficult to fully include these children in the school environment. Teacher training is a key element in building a pedagogical practice that is sensitive and adapted to the specific needs of children with ASD. In addition, adequate infrastructure and the presence of support professionals are essential to guarantee an environment that is conducive to learning and development. Family involvement and coordination between the school's various professionals are also pointed out as factors that contribute to successful inclusion. The article also highlights the importance of diversified teaching practices that value the uniqueness of each child and promote their autonomy, socialization and well-being. It highlights the need for a cultural change in educational institutions, which must overcome traditional models and value diversity as a pedagogical and ethical principle. The collective commitment of educators, managers, families and public policy makers is fundamental to guaranteeing the rights of children with ASD and building inclusive schools. The study reinforces that inclusion in early childhood education is a continuous and dynamic process that requires training, investment and awareness-raising, representing an opportunity to build a fairer, more democratic and plural society.